Dalbavancin to facilitate early discharge in the treatment of complex musculoskeletal infections: a multi-centre real-life application - T. Azamgarhi; S. Warren; A. Scobie; N. Karunaharan; C. Perez-Sanchez; R. Houghton; S. Hassan; J. Lourtet-Hascoët; J. Lourtet-Hascoët; H. Kershaw; P. Sendi; K. Saeed; et al. (Journal of Bone and Joint Infection)
Dalbavancin is a lipoglycopeptide with a half-life of 14 d, significantly reducing the need for daily antibiotic dosing. Although dalbavancin is approved for acute bacterial skin and skin structure infections, its off-label use in complex musculoskeletal infection (MSKI) is increasing. Evidence on its effectiveness for MSKI, especially in facilitating early discharge for patients unsuitable for oral or OPAT (outpatient parenteral antimicrobial therapy) treatments, is limited.